The Role Of Knowledge Management In Increasing Organizational Flexibility To Face The Changes Brought By The Industrial Revolution 4.0 - Herman Oddyansyah Felani; Wahyuningsih Santosa; Panca Purakusuma Idris (Eduvest - Journal of Universal Studies, 2024)
The importance of knowledge management integration in increasing organisational flexibility in the midst of the Industrial Revolution 4.0, which demands rapid adaptation and responsiveness, requires organisations to continue to innovate in the dynamics of change. The purpose of this study is to explore the relationship between knowledge management and organisational flexibility and provide practical recommendations to optimise the application of knowledge management to improve organisational responsiveness. The research method uses a qualitative approach with literature study as the main source of data. The results revealed that effective integration between knowledge management and organisational flexibility can provide a significant competitive advantage. However, in its implementation, there are obstacles such as cultural resistance and technological limitations. The conclusion of this study confirms that a thorough and integrated application of knowledge management is the key to increasing organisational flexibility in the digital era. The implication of these findings is the need for organisational commitment to build a culture of knowledge sharing, adopt technologies that support knowledge management and align strategies with overall business objectives to ensure success in the face of change and maintain competitiveness in a dynamic market.